2021
DOI: 10.3390/ijms22052400
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Determinants of the Kinetic Binding Properties of Antihistamines at the Histamine H1 Receptors

Abstract: The binding affinity of ligands for their receptors is determined by their kinetic and thermodynamic binding properties. Kinetic analyses of the rate constants of association and dissociation (kon and koff, respectively) of antihistamines have suggested that second-generation antihistamines have a long duration of action owing to the long residence time (1/koff) at the H1 receptors. In this study, we examined the relationship between the kinetic and thermodynamic binding properties of antihistamines, followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…This is a hot area of pharmacological research, pioneered by histamine receptorologists. Kinetic binding properties using QSAR analyses showed that although the binding enthalpy and entropy might contribute to the increase and decrease, respectively, in the koff values, there was no significant relationship with the kon values [3].…”
mentioning
confidence: 96%
“…This is a hot area of pharmacological research, pioneered by histamine receptorologists. Kinetic binding properties using QSAR analyses showed that although the binding enthalpy and entropy might contribute to the increase and decrease, respectively, in the koff values, there was no significant relationship with the kon values [3].…”
mentioning
confidence: 96%